Analisa kerja alat uji prestasi mesin pendingin udara dengan kapasitas daya kompresor 1 PK - Lukito Dwi Yuono; Eko Budiyanto; Ari Ansori (TURBO [Tulisan Riset Berbasis Online], 2022)
The purpose of the study was to determine the temperature value at each point of the refrigeration performance tool, heat absorption, refrigerant flow rate, compressor power, and the working speed of the refrigeration performance test tool or (Coefficient Of Performance) COP during the 60 minute test time. The method that will be used in this research is to modify the test equipment and conduct real experiments by analyzing several variables that affect the performance of the air conditioning system. The independent variables in this study were the refrigerant pressure of 60 Psi, 70 Psi, and 80 Psi. The addition of several components of measuring instruments that function to display data will be carried out at each point as needed. Digital reading of data will function to display test result data in the form of numbers for air temperature, temperature, and refrigerant pressure in the air conditioning machine (AC). The study was conducted in a room with a size of 4 x 5 x 2.5 meters, and using LG AC with a compressor power of 1 PK. Based on the test results, changes in temperature that occur at each point of the performance of the air conditioning machine and heat absorption affect the temperature changes of each cooling machine performance, namely the use of 60 Psi of 23.9 C for 70 Psi of 24.8 C and 80 Psi is 22.1 C. Then changes to heat absorption by the condenser and evaporator are at a refrigerant pressure of 60 Psi of 171.6 kJ/s for 70 Psi of 201.1 kJ/s and 80 Psi of 215.3 kJ/s. And the heat absorption that occurs in the evaporator with a pressure of 60 Psi is 143.3 kJ/s for 70 Psi of 161.6 kJ/s and 80 Psi is 172.2 kJ/s. The resulting refrigerant flow rate and compressor power, for the refrigerant flow rate, affect the changes that occur in the use of 60 Psi of 0.003 kg/s, for 70 Psi of 0.004 kg/s, and 80 Psi of 0.005 kg/s. Then for the compressor power at the use of 60 Psi of 0.446 kW, for 70 Psi of 0.521 kW, and 80 Psi of 0.611 kW. The refrigerant flow rate value of the refrigeration machine performance test tool or COP produced at a refrigerant pressure of 60 Psi is 3.26 for 70 Psi, namely 4.45 and 80 Psi is 5.11.